A flu optical immunoassay (ThermoBioStar's FLU OIA): a diagnostic tool for improved influenza management. - Tucker, S P (2001)
ThermoBioStar's and Biota's flu optical immunoassay (FLU OIA) is a rapid test designed to diagnose influenza A and B infection using a variety of specimen types. The assay uses highly sensitive thin-film detection methods, coupled with specific monoclonal antibodies to the nucleoprotein. The test is simple to perform, requires no instrumentation and is intended to provide a result within 15 min of test initiation in the 'point-of-care' environment. In initial clinical studies, the assay was demonstrated to be equivalent to culture in identifying infected individuals. Subsequent independent studies using a variety of sample types have demonstrated sensitivity ranging from 48 to 100% and specificities ranging from 93 to 97%. In addition to detecting human strains, this assay has been demonstrated to be capable of detecting a variety of avian and non-human mammalian influenza viruses. The FLU OIA test has been used in large-scale surveillance schemes intended to provide rapid epidemiological data during normal influenza seasons and has demonstrated the potential for fulfilling a similar role for multispecies surveillance in, for example, conditions that offer challenges for conventional virus isolation methods. Conceivably, such use should facilitate the timely recognition of influenza outbreaks and prioritization of positive specimens for more conventional, laboratory characterization, leading to improved interpandemic surveillance and rapid reaction in the face of the next pandemic.